Somatosensory evoked magnetic fields of periodontal mechanoreceptors. Issue 1 (January 2020) - Hihara, Hiroki; Kanetaka, Hiroyasu; Kanno, Akitake; Shimada, Eriya; Koeda, Satoko; Kawashima, Ryuta; Nakasato, Nobukazu; Sasaki, Keiichi
Abstract: To evaluate the localization of responses to stimulation of the periodontal mechanoreceptors in the primary somatosensory cortex, somatosensory evoked fields (SEFs) were measured for stimulation of the left mandibular canine and first molar using magnetoencephalography in 25 healthy subjects. Tactile stimulation used a handmade stimulus device which recorded the trigger at the moment of touching the teeth.SEFs for the canine and first molar were detected in 20 and 19 subjects, respectively. Both responses were detected in the bilateral hemispheres. The latency for the canine was 62.1 ± 12.9 ms in the ipsilateral hemisphere and 65.9 ± 14.8 ms in the contralateral hemisphere. The latency for the first molar was 47.4 ± 6.6 ms in the ipsilateral hemisphere and 47.8 ± 9.1 ms in the contralateral hemisphere. The latency for the first molar was significantly shorter than that for the canine. The equivalent current dipoles were estimated in the central sulcus and localized anteroinferiorly compared to the locations for the SEFs for the median nerve. No significant differences in three-dimensional coordinates were found between the canine and first molar. These findings demonstrate the precise location of the teeth within the orofacial representation area in the primary somatosensory cortex. Abstract : Physiology; Nervous system; Dentistry; Medical imaging; Clinical research; Neuroscience; Neurology; Somatosensory evoked fields; Periodontal mechanoreceptor; Canine; First molar; Primary somatosensory cortex.